História natural de Sibon nebulatus (Linnaeus 1758) (Dipsadidae; Dipsadini) em enclaves de florestas úmidas altitudinais do Ceará, Nordeste, Brasil - Sousa, Átilas Rodrigues de (2024)
The ecological niche theory relates to various ecological issues, including the distribution, abundance, and diversity of species, and is closely linked to conservation. Natural history helps us understand the functioning and organization of the niche, involving investigations into the use of space, reproduction, parasitism, and diet of individuals. The importance of knowing such aspects of an organism’s ecology is closely related to its conservation, especially when we refer to those living in highly threatened relict environments or those that present high cryptic diversity. Sibon nebulatus is a species of snake widely distributed in the Neotropical region, involving a complex of species with relict populations in fragmented habitats. Few works report the general biology of this species, there are gaps in knowledge about its trophic and parasitic ecology, as is the case with other snakes that do not have medical interest. Having this data can help us identify the specific environments it is capable of occupying and the ideal conditions for its survival, providing support for biogeographic studies. Therefore, this work intended to describe fundamental aspects of its ecology, specifically its feeding and parasitic biology. We statistically analyzed its trophic niche width and host-parasite relationships. We initially predicted that this species would show ecological patterns very similar to those of other species in its tribe, reflecting not only the environment but also the phylogeny. In this study, Sibon nebulatus proved to be a specialist predator in the consumption of terrestrial gastropods, mainly without shells, presenting a low food niche amplitude. Gastropods of the Veronicellidae family are its main prey. We added 3 unpublished records of parasites infecting this species: Cruzia sp., Oswaldocruzia sp. and Mesocoelium monas. In addition, we did not find correlations between the host’s body measurements and parasite abundance. There is also no correlation between parasite abundance and host sex. We hope that these results can add more knowledge about the ecology of Neotropical species, complementing concrete and public databases that provide support for various areas of knowledge, including, mainly, species conservation.